Diagnostic accuracy of Instrumental Activities of Daily Living for dementia in community-dwelling older adults - Mao, Hui-Fen; Chang, Ling-Hui; Tsai, Athena Yi-Jung; Huang, Wen-Ni Wennie; Tang, Li-Yu; Lee, Huey-Jane; Sun, Yu; Chen, Ta-Fu; Lin, Ker-Neng; Wang, Pei-Ning; Shyu, Yea-Ing Lotus; Chiu, Ming-Jang (Age and ageing, 2018)
Abstract Background many people living with dementia remain underdiagnosed and unrecognised. Screening strategies are important for early detection. Objective to examine whether the Lawton’s Instrumental Activities of Daily Living (IADL) scale, compared with other cognitive screening tools—the Mini-Mental State Examination (MMSE), and the Ascertain Dementia 8-item Informant Questionnaire (AD8)—can identify older (≥ 65 years) adults with dementia. Design population-based cross-sectional observational study. Setting all 19 counties in Taiwan. Participants community-dwelling older adults (n = 10,340; mean age 74.87 ± 6.03). Methods all participants underwent a structured in-person interview. Dementia was identified using National Institute on Aging-Alzheimer’s Association core clinical criteria for all-cause dementia. Receiver operator characteristic curves were used to determine the discriminant abilities of the IADL scale, MMSE and AD8 to differentiate participants with and without dementia. Results we identified 917 (8.9%) participants with dementia, and 9,423 (91.1%) participants without. The discriminant abilities of the MMSE, AD8 and IADL scale (cutoff score: 6/7; area under curve = 0.925; sensitivity = 89%; specificity = 81%; positive likelihood ratio = 4.75; accuracy = 0.82) were comparable. Combining IADL with AD8 scores significantly improved overall accuracy: specificity = 93%; positive likelihood ratio = 11.74; accuracy = 0.92. Conclusions our findings support using IADL scale to screen older community-dwelling residents for dementia: it has discriminant power comparable to that of the AD8 and MMSE. Combining the IADL and the AD8 improves specificity.